Vegetation Distribution Patterns in the Mangrove Forest Area of Teluk Buo Tourism Village, West Sumatera - Marbun, Duma Erza; Putri, Irna Leilani Eka (Jurnal Serambi Biologi, 2024)
Vegetation is a plant community that can be found in a landscape or geographic area. Vegetation has the ability to adapt to its environment and has an important role in terms of hydrology and climate change. Teluk Buo Beach, which is located in Teluk Buo Tourism Village, Teluk Kabung Tengah Village, Bungus District, Padang City, West Sumatra, has various types of coastal vegetation. The vegetation that can be found in the Teluk Buo Beach area is herbaceous vegetation, shrubs and trees. Dispersal Pattern is a movement separating individuals or population groups from the vegetation population itself and this movement is closely related to environmental conditions. This research aims to determine the distribution pattern of vegetation on Teluk Buo Beach, West Sumatra. The research method implemented was the quadratic method. The vegetation found was 7 species, namely Rhizophora apiculata, Bruguiera gymnorhiza, Setaria palmifolia, Nypa Fruticans, Bruguiera gymnorhiza, Euterpe oleracea mart., and Lumnitzera littorea. In herbaceous habitus vegetation, the distribution pattern is random with a morisita degree value obtained at 0.23, namely IP = 0, for bush and tree habitus vegetation, the morisita degree value obtained is -11.91 and -12.47 based on the criterion of P < 0, namely distribution pattern. uniformly.